The role of biocatalysts in the synthesis of graphene nanosheets from sub-bituminous coal - Purwandari, Vivi (2024)
The synthesis of graphene nanosheets (GNs) from sub-bituminous coal aims to increase the added value of coal in a cheap, easy and proclaimed this method on an industrial scale. The addition of biocatalyst (BFS) in the pyrolysis process can reduce the reactive temperature of the pyrolysis process so that the combustion reaction runs better at low temperatures of 200-300℃. Followed by hydrothermal carbonization of coal at 180℃ for 6 h with the addition of pyrolysis liquid smoke. Filter the results and exfoliate using 24 kHz ultrasonication for 30 min. Then centrifuge at 10,000 rm for 10 min to separate the solids. Wash the solids with deionized water to obtain a neutral pH. Using FESEM and TEM to obtain the morphological characteristics of GNs, structural characterization was studied using XPS, FTIR, and XRD. The GNs produced using BFS yielded 7–8 layers of Graphene, and a crystal size of 2.7 nm showing promising efficiency from the methodology used.